บุญช่วย ศรีสวัสดิ์: ผู้ประกอบการ ปัญญาชน และนักการเมือง กับความเปลี่ยนแปลงของเชียงรายและสังคมไทย - ทศพล ศรีนุช (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objective of this thesis is to study the role of Boonchuey Srisavasdi as an entrepreneur, politician and intellectual by considering these in relation to economic, social, political and cultural changes in Chiang Rai Province and Thailand. The findings demonstrate that Boonchuey Srisavasdi had a family background and life experience in Chiang Rai Province, Thai society and Japanese society. This helped make him to develop a "Sense of entrepreneurship" and eager to invest in goods production and trade, aspiring to seek and create new knowledge, which would be disseminated to the public. Knowledge created by Boonchuey Srisavasdi did not only meet the need of The Thais to understand the changes in Thailand and in the global society after World War 2, but also aimed to make Thai people recognize the importance of solving various issues at the national level, including the poverty of people in the north, and help support the development of Chiang Rai, Northern region and Thailand as a whole. It can be said that the intellectual role of Boonchuey Srisavasdi comes from his awareness as an entrepreneur who would like to establish the economic growth for himself and society. This aspiration encouraged Boonchuey Srisavasdi to be come the national politician who was elected as a representative of Chiang Rai Province many times. The ethnography he conducted and published was a result of the effort to make Thai people aware of the diversity of people living in Thai territory. Such ethnographic work emphasizes the truth that "Northern people are Thais" so that the support on development and tourism should be contributed to the Northern region. Being a politician offered a chance to Boonchuey Srisavasdi to propose solutions and development ideas at the provincial, regional and national levels. The roles of Boonchuey Srisavasdi as an entrepreneur, politician and intellectual were highly interrelated.